KEARIFAN TRADISI AL-QUR’AN DALAM PROSES ENKULTURASI BUDAYA LOKAL - Ansori Ansori (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Islam Negeri Profesor Kiai Haji Saifuddin Zuhri Purwokerto Purwokerto, 2011)
This article shows the Qur’an’s wisdom on social transformation.The enculturation wisdom offered by The Qur’an is clearly showed on itsverses. Those wisdoms follow a certain pattern which started by first,admitting local traditions second, processing those local traditions by refusingsome of them in humanism consideration. Finally, a judgment istaken by refusing or accepting it with some modification. The missionoffered is intended to reach the moral goodness, create and protect thesocial order and it’s equilibrium.